2021
DOI: 10.1039/d0tb01880e
|View full text |Cite
|
Sign up to set email alerts
|

Pre-targeting with ultra-small nanoparticles: boron carbon dots as drug candidates for boron neutron capture therapy

Abstract: Boron neutron capture therapy (BNCT) is a promising cancer treatment exploiting the neutron capture capacity and subsequent fission reaction of boron-10. The emergence of nanotechnology has encouraged the development of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Such an effect results from the presence of leaky vasculature and deficient lymphatic drainage in the vicinity of tumors, which ultimately results in the passive accumulation of nontargeted nanosized materials in the tumor tissue after intravenous administration. A plethora of nanostructured materials that rely on the EPR effect have been proposed as boron delivery agents, including liposomes, carbon nanotubes, boron nitride nanotubes, magnetic nanoparticles, , boron carbide nanoparticles, , borosilicates, gold nanoparticles, , and carbon dots . Noteworthily, the EPR effect is a highly heterogeneous phenomenon, which varies substantially among different tumor types, patients, and even regions within a single tumor. , As a consequence, the extravasation of boron-rich nanomedicines may follow a heterogeneous pattern and lead to suboptimal treatment efficacy due to the short range of recoil ions generated upon neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect results from the presence of leaky vasculature and deficient lymphatic drainage in the vicinity of tumors, which ultimately results in the passive accumulation of nontargeted nanosized materials in the tumor tissue after intravenous administration. A plethora of nanostructured materials that rely on the EPR effect have been proposed as boron delivery agents, including liposomes, carbon nanotubes, boron nitride nanotubes, magnetic nanoparticles, , boron carbide nanoparticles, , borosilicates, gold nanoparticles, , and carbon dots . Noteworthily, the EPR effect is a highly heterogeneous phenomenon, which varies substantially among different tumor types, patients, and even regions within a single tumor. , As a consequence, the extravasation of boron-rich nanomedicines may follow a heterogeneous pattern and lead to suboptimal treatment efficacy due to the short range of recoil ions generated upon neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, only two boron-containing compounds, (L)-4-dihydroxy-borylphenylalanine (BPA, 1 ) and sodium mercaptoundecahydro- closo -dodecarborate (BSH, 2 ) ( Figure 3 A), are currently available as BNCT agents in clinical use. 37 This may be ascribed to the low selectivity for cancer cells except for brain tumors as well as head and neck cancers (HNC). 38
Figure 2 How BNCT kills tumor cells
Figure 3 Applications of carboranes in BNCT
…”
Section: Applications Of Carboranes As Boron Neutron Capture Therapy Agentsmentioning
confidence: 99%
“…On the other hand, biodistribution studies in a xenograft mouse model of human fibrosarcoma showed major accumulation in the liver, lungs and spleen. These results indicate the necessity of further optimization in terms of shape and size of the gold nanoparticles and pre-targeting might be an option [98]. Gold nanoparticles (NP) coated with the boron-rich cobalt bis(dicarbollide) anion and stabilized with polyethylene glycol were synthesized (Figure 10) [49].…”
Section: Figurementioning
confidence: 99%
“…On the other hand, biodistribution studies in a xenograft mouse model of human fibrosarcoma showed major accumulation in the liver, lungs and spleen. These results indicate the necessity of further optimization in terms of shape and size of the gold nanoparticles and pre-targeting might be an option [98]. Recently, Feiner et al [98] investigated a pre-targeting strategy using ultra-small nanoparticles (boron-rich carbon dots) to reduce off-target side effects caused by long circulations times during application of normal nanocarriers.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation